1985
DOI: 10.1099/0022-1317-66-8-1763
|View full text |Cite
|
Sign up to set email alerts
|

Retrieval of Latent Herpes Simplex Virus Type 1 Genetic Information from Murine Trigeminal Ganglia by Superinfection with Heterotypic Virus in vivo

Abstract: SUMMARYMice previously latently infected with the F strain of herpes simplex virus type 1 (HSV-1) can be successfully colonized with a second virus strain if HSV-2 is introduced at the same peripheral site as HSV-1. On the other hand, HSV-1 strains seemed able mutually to exclude establishment of latency with each other. Mice (3 months or 3 years after nasal infection) latently infected with HSV-1 were thus superinfected with HSV-2. The mice were sacrificed 2 days post-infection when HSV-2 replication in the g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
3

Year Published

1987
1987
2009
2009

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 26 publications
0
8
3
Order By: Relevance
“…Since BHV 1.1 (IBRV) and BHV 1.2a and 1.2b (IPVV) share 95% sequence homology and are indistinguishable serologically, this would be analogous to 2 different strains of HSV 1 establishing latency at the same site. Our findings contrast with previous reports on HSV 1 that indicate only the primary infecting herpesvirus establishes latency [4,10,25] or that the primary infecting herpesvirus induces a state of resistance to colonization by the second virus [12], and confirm and extend what has been reported for HSV2 [1][2][3] and BHV1 [17,18].…”
Section: Discussioncontrasting
confidence: 77%
See 1 more Smart Citation
“…Since BHV 1.1 (IBRV) and BHV 1.2a and 1.2b (IPVV) share 95% sequence homology and are indistinguishable serologically, this would be analogous to 2 different strains of HSV 1 establishing latency at the same site. Our findings contrast with previous reports on HSV 1 that indicate only the primary infecting herpesvirus establishes latency [4,10,25] or that the primary infecting herpesvirus induces a state of resistance to colonization by the second virus [12], and confirm and extend what has been reported for HSV2 [1][2][3] and BHV1 [17,18].…”
Section: Discussioncontrasting
confidence: 77%
“…A question about latency that has remained unresolved is whether two herpesviruses can establish latency at the same site within an animal. Data from experiments with HSV 1 show that prior colonization of a ganglion with HSV 1 either precludes its superinfection with another HSV 1 strain of at least the same serotype [4,25], or induces a state of' resistance to colonization of the ganglion by a second infecting virus [ 12]. Observations that this may not be the case have been reported for HSV2 [3] and BHV t [17,18].…”
Section: Introductionmentioning
confidence: 96%
“…The simplest explanation may be that the same neuron can be superinfected by different strains. Conflicting data has been reported from animal models, where some authors have shown that the same ganglia can be superinfected by a new HSV-1 strain (Meignier et al, 1983), whilst others have shown the preclusion of a superinfecting strain (Centifanto-Fitzgerald et al, 1982;Mador et al, 2002;Thomas et al, 1985). Data from humans are sparse, but single human trigeminal neurons can be dually infected by HSV-1 and varicellazoster virus (Theil et al, 2003) and, although rare, multiple HSV-1 strains have been recovered from the same human trigeminal ganglia (Lewis et al, 1984).…”
Section: Discussionmentioning
confidence: 85%
“…[7][8][9][10] This results in a recrudescence of dormant viral particles leading to inflammation, swelling, and entrapment. 11 The herpesviruses constitute a DNA virus group that includes the herpes simplex (HSV) and herpes zoster viruses.…”
Section: Clinical Challenges In Otolaryngologymentioning
confidence: 99%